The effect of a four week aerobic training on serum levels of irisin and insulin resistance in women with type 2 diabetes - Faranak Balaghi Inaloo; Farzaneh Abolfathi; Mehrzad Shabani; Aliakbar Alizadeh (مجله دانشگاه علوم پزشکی بیرجند, 2017)
Background and Aim: Physical activity is an appropriate cost-effective means for the prevention and treatment of type II diabetes. Irisin, a recently identified myokine seems to have an important role in the transformation of white fat tissue and regulation of insulin sensitivity. The current study aimed at investigating the effect of aerobic training on serum levels of irisin and insulin resistance in women with type II diabetes. Materials and Methods: In this semi- experimental study, 24 women with type II diabetes were objectively selected and randomly assigned into two equal groups of aerobic training and control. The exercise group undertook a 4 week (5 times a week) run aerobic exercise on a treadmill with 55-80 percent of maximum heart rate intensity. The control group did not have any physical activities. Blood samples were taken before and 48 hours after the last training session and serum levels of blood glucose and insulin were assessed. The obtained data was analyzed using paired t-test and covariance analysis. The significant level was P<0/05. Results: The Results showed significant increase in the irisin and reduce in insulin resistance and glucose in exercise group compared with the control group (P<0/05) the difference between the two groups was significant in the irisin and glucose (P<0/05). Also There is no significant correlation between irisin and insulin resistance (P<0/05). Conclusion: Aerobic exercise, through a favorable impact on irisin levels and insulin resistancecan act as an effective factor to improve the complications in type II diabetics.